2004
DOI: 10.1002/cncr.20232
|View full text |Cite
|
Sign up to set email alerts
|

β‐Catenin and p53 analyses of a breast carcinoma tissue microarray

Abstract: BACKGROUNDAberrant activation of the β‐catenin signaling pathway has been implicated in several malignancies, including breast carcinoma. Recently, it was shown that p53 down‐regulated β‐catenin in a complex fashion. The authors examined the expression of β‐catenin, key members of its signaling pathway, and p53 in a large cohort of breast tumors.METHODSThe authors conducted an immunohistochemical analysis of the expression of β‐catenin, upstream modulators (HER‐2/neu, Met, and epidermal growth factor receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
59
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 29 publications
7
59
1
1
Order By: Relevance
“…Given the role of P53 in apoptosis, observing high levels of P53 in a pathology sample is indicative of mutation in the P53 apoptotic pathway. Therefore, the findings of Chung et al (2004) are consistent with our results that the combination of aberrant b-catenin and dysfunctional P53 leads to a more aggressive and metastatic tumor. These results have important implications related to the usefulness of multiple prognostic markers when analyzing tumors in the clinic.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Given the role of P53 in apoptosis, observing high levels of P53 in a pathology sample is indicative of mutation in the P53 apoptotic pathway. Therefore, the findings of Chung et al (2004) are consistent with our results that the combination of aberrant b-catenin and dysfunctional P53 leads to a more aggressive and metastatic tumor. These results have important implications related to the usefulness of multiple prognostic markers when analyzing tumors in the clinic.…”
Section: Discussionsupporting
confidence: 91%
“…Chung et al (2004) observed that the presence of high levels of b-catenin protein in combination with high levels of P53 in the primary tumors of lymph node negative breast cancer patients correlated with a worse survival than patients displaying high levels of either protein alone. Given the role of P53 in apoptosis, observing high levels of P53 in a pathology sample is indicative of mutation in the P53 apoptotic pathway.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Immunohistochemical staining carried out by several groups has demonstrated elevated levels of nuclear and/or cytoplasmic b-catenin in breast tumours with significant frequency (Lin et al, 2000;Ryo et al, 2001;Chung et al, 2004). Lin et al (2000) also showed that nuclear and/or cytoplasmic staining of b-catenin correlated with elevated cyclin D1, which is one of the known targets of b-catenin/TCF transcription.…”
Section: Discussionmentioning
confidence: 99%
“…This signalling pathway is strongly implicated in tumorigenesis; indeed, the first mammalian Wnt isoform was identified based on its ability to promote mouse mammary tumorigenesis (Polakis, 2000). In addition, aberrant nuclear and cytoplasmic localisation of b-catenin is frequently observed in human breast cancer (Lin et al, 2000;Ryo et al, 2001;Chung et al, 2004). In contrast to colorectal cancer (CRC), however, mutation of APC, AXIN or CTNNB1 (b-catenin) is rare in breast cancer, indicating that other mechanisms are responsible for the activation of b-catenin.…”
mentioning
confidence: 99%